Prevalence of asymptomatic bacteriuria among elderly diabetic patients residing in Chitwan - Jha, BK; Singh, YI; Khanal, LK; Yadab, VC; Sanjana, RK (Kathmandu University Medical Journal, 2010)
Background: A retrospective study was done on Asymptomatic Bacteriuria (ASB), among elderly diabetic patients residing in Chitwan, Nepal from 1st January 2006 to 12th December 2006. Diabetic patients above 40 years of age were included in this study where as below 40 years of age group were excluded. Objective: To study the prevalence of ASB among elderly diabetic patients for the Bacteriological profile and their antibiotic susceptibility pattern. Materials and methods: Urine sample was collected from 636 diabetic patients above 40 years age attending College of Medical Sciences Teaching Hospital for regular blood sugar estimation. Culture and Antibiotic susceptibility test (AST) were performed using standard microbiological technique. ASB was determined as presence of ≥ 105 bacteria/ml in a culture of urine sample. Results: The prevalence of ASB among diabetic patients in Bharatpur was found to be 9.43% (12.07% in females and 5.08% in males). The most common bacterial isolate was Escherichia coli (41.66%). Nitrofurantoin, Cefotaxime and Chloramphenicol were the most effective drugs for the majority of isolates. Conclusion: The study shows necessity of regular urine culture to detect ASB, along with blood sugar estimation for diabetic patients to prevent them from further complications due to it. Key words: Diabetic; ASB; Common pathogen and AST DOI: 10.3126/kumj.v7i2.2712 Kathmandu University Medical Journal (2009) Vol.7, No.2 Issue 26, 157-161